Rheological Properties Of Asphalt Binders, Performance And Sustainability Of Warm-Mix Asphalt Incorporating Sasobit® - Jamshidi, Ali (2013)
Pavement construction consumes a significant amount of depleting non-renewable natural resources, including asphalt binder and aggregate and energy. Therefore, new and cost-effective technologies in the pavement construction are required to be fewer dependants on the non-renewable natural sources, such as energy and materials. One of such technologies is warm mixture asphalt (WMA). One of additives used to produce WMA is a type of synthetic wax called Sasobit®. In this thesis, overall results of rheological binder tests indicated that Sasobit® content and asphalt binder type had significant effects on rheological parameters of asphalt binders in terms of viscosity, G*/sin δ, G*sin δ, asphalt flow, Jnr, percent recovery. The results also indicated that non-dimensional viscosity index (Sη∇), non-dimensional Superpave™ rutting factor (NSRP) and threshold of non-Newtonian flow (TNF) were useful parameters to explain the changes of rheological properties of Sasobit®-modified asphalt binders influenced by different conditions such as aging, test temperature and shear rate. For example, analysis of Sη∇ indicated the relative viscosity of the binder sample reduces by 7% for every 1% Sasobit® content added. At higher temperatures ranging from 150°C to 160°C, the value of ∇ηS reduces to 4.1%. The general outputs of mixture performance tests showed that performance of Sasobit®-WMA samples in terms of indirect tensile strength, resilient modulus, creep stiffness and cumulative micro-strains depended on Sasobit® content, construction and testing temperatures. Although aggregate supplied from different sources can be the same type with similiar properties such as specific gravity, their specific heat capacity coefficient (C) can be very different.